The use of European funds for tourism development in coastal communes on the Baltic Coast - Parzych, Krzysztof (Turyzm/Tourism, 2017)
The article discusses the use of financial resources from European funds for tourism development in coastal communes on the Baltic Coast in Poland. A detailed analysis of the use of EU funds has been carried out, with particular emphasis on those priorities which are related to the improvement of the tourism attractiveness of coastal communes and to their tourism development. The analyses have been made on the basis of data from the Ministry of Regional Development concerning the allocation of European funds in 2007-13.